Disaster Management of Archives in Indonesia: A Systematic Literature Review - Jalinur Jalinur; Rahmi Rahmi (Program Studi Kearsipan, DBSMB SV UGM, 2021)
Archives are vital assets to organizations, communities and individuals. Recovering archives from natural and human-made disasters requires careful handling. Governments, agencies, and the private sector must plan and prepare for archive rescue management, the main objective of which is the long-term preservation of documents and archives. This study aims to determine models of disaster affected archive management and to assess challenges to managing disasters in archives in Indonesia by performing a systematic literature review of journal articles published from 2015 to 2020. The results show that the selected journal articles primarily focused on disaster prevention, while disaster recovery was not widely discussed in journal articles from Indonesia. This research examines the suitability of models presented in the literature to manage and rescue archives relative to Indonesia’s rules and existing models and methods.